Legal Status of Profession Waqf from a Positive legal Perspective in Indonesia - Dwi Putri Nirmala, Rindang; Adzantyassurya Qotrunnada, Amara Srie; Mahmada, Elya; Nida Tahaanii, Aanisah; Andhita Putri, Karin (Journal of Law, Politic and Humanities, 2024)
This research paper, "Legal Status of Profession Waqf from a Positive Legal Perspective in Indonesia," explores the emergence of a new form of waqf called profession waqf, where individuals donate their professional skills for public welfare, necessitating clear legal regulations. Building upon previous research, this study aims to establish a legal framework that aligns with Islamic principles and Indonesian law to maximize the potential of profession waqf. Using a normative legal research method, the study reviews primary and secondary legal materials to understand the legal status of profession waqf in Indonesia. The findings aim to bridge the regulatory gap and optimize the societal benefits of profession waqf, particularly in supporting religious activities, education, and health services. Waqf holds great potential to enhance the welfare of Indonesian society and is continuously evolving. The Indonesian Waqf Board (BWI), as the governing body for waqf management in Indonesia, has introduced several contemporary forms of waqf, including profession waqf. Profession waqf involves contributing human knowledge and skills in physical and non-physical domains. This research aims to understand the concept of profession waqf and its subjects in practice in Indonesia. The findings indicate that profession waqf involves endowing one's profession or expertise for the common good of society following applicable legal regulations. The subjects of waqf include the Waqif Profession, who contributes their skills or profession; the nazir, who manages the waqf assets; and the mauquf alaih, the beneficiaries of the waqf, which may be specified directly in the waqf deed or declaration or not specifically mentioned.